A Study on the Resilience of Adolescents in Orphanages in Achieving the Sustainable Development Goals - Pulungan, Syakirah Tazkiyah; Az-Zahra, Shofi Atiqah; Hasibuan, Rini Syahrayni (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The research on resilience among adolescents in orphanages has been extensively explored; however, the relationship between the literature on the role of Sustainable Development Goals (SDGs) in developing resilience remains underexamined. Therefore, one of the objectives of this study is to investigate the role of psychoeducation using positive thinking training techniques in enhancing the resilience of adolescents in orphanages. A total of 18 adolescents participated, divided equally into a psychoeducation group (n = 9) and a control group (n = 9). The instrument utilized in this study was the resilience scale developed by Daulay and Indriani (2024). Data analysis was conducted using independent sample t-tests. The results indicate that there is significant difference in resilience between the psychoeducation and control groups (F(1,15) = 2.836, t = -2.302, p < 0.05), with the control group exhibiting higher resilience in the post-test condition (n = 9; M = 57.00; SD = 14.221) compared to the psychoeducation group (n = 9; M = 64.13; SD = 8.254). The implications of this research underscore that adolescents who successfully navigate their challenges and demonstrate resilience represent a crucial aspect of socialization reflecting the significance of the Sustainable Development Goals in fostering a golden generation by 2045.Penelitian mengenai resiliensi di kalangan remaja di panti asuhan telah banyak dieksplorasi; namun, hubungan antara literatur mengenai peran Tujuan Pembangunan Berkelanjutan (SDGs) dalam mengembangkan resiliensi masih belum banyak diteliti. Oleh karena itu, salah satu tujuan penelitian ini adalah untuk menyelidiki peran psikoedukasi dengan menggunakan teknik pelatihan berpikir positif dalam meningkatkan resiliensi remaja di panti asuhan. Sebanyak 18 remaja berpartisipasi, dibagi secara merata ke dalam kelompok pendidikan psikologis (n = 9) dan kelompok kontrol (n = 9). Instrumen yang digunakan dalam penelitian ini adalah skala resiliensi yang dikembangkan oleh Daulay dan Indriani (2024). Analisis data dilakukan menggunakan uji t sampel independen. Hasil menunjukkan adanya perbedaan yang signifikan dalam resiliensi antara kelompok psikoedukasi dan kelompok kontrol (F(1,15) = 2.836, t = -2.302, p < 0.05), dengan kelompok kontrol menunjukkan resiliensi yang lebih tinggi pada kondisi pasca-tes (n = 9; M = 57.00; SD = 14,221) dibandingkan dengan kelompok psikoedukasi (n = 9; M = 64,13; SD = 8,254). Implikasi penelitian ini menekankan bahwa remaja yang berhasil mengatasi tantangan mereka dan menunjukkan resiliensi merupakan aspek krusial dalam proses sosialisasi, yang mencerminkan pentingnya Tujuan Pembangunan Berkelanjutan (SDGs) dalam membina generasi emas pada tahun 2045.